(untitled) - Sandy, Chuck; Chuck Sandy; Curtis Kelly; series consultant: Neil J. Anderson (Boston)
Active Skills for Communication is an exciting new three-level series that develops learners' speaking and listening skills. Written by ELT specialists Curtis Kelly and Chuck Sandy, with series consultant Neil J. Anderson, the series uses the ACTIVE approach to help learners become more fluent, confident - and active - speakers of English. Each unit contains easy-to-follow, step-by-step activities that lead toward a major speaking task. The tasks are based on real-life situations and are designed to increase self confidence and foster positive attitudes towards learning English
Keywords: Oral communication; Interpersonal communication